Neuronal TDP-43 regulates myelin formation via neurexin 1 mRNA stabilization - Jiayi Li; Yohei Iguchi; Kenji Yoshida; Daisuke Kato; Kunihiko Araki; Kenta Kobayashi; Satoshi Yokoi; Rei Yoshimoto; Madoka Iida; Yoshinobu Amakusa; Yu Kawakami; Takashi Yoshimura; et al. (Proceedings of the National Academy of Sciences, 2026)
Amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) develop as spatial pathologies in which neurons and glial cells are interconnected. TAR DNA-binding protein 43 (TDP-43) is a major pathological protein that is inextricably associated with ALS and FTLD. In this study, we investigated the roles of neuronal TDP-43 in neuron–oligodendrocyte interactions using neuron-specific TDP-43 knockout (TDP-43cKO) mice. TDP-43 depletion in neurons induced hypomyelination, which was confirmed by immunohistochemistry and ultrastructural analysis. In addition, conduction disturbance was revealed by electrophysiological analysis. The hypomyelination of TDP-43cKO mouse was restored by cytoplasmic TDP-43 supplementation in neurons. Neuron-specific transcriptome analysis revealed that neurexin 1 (NRXN1) is the regulatory target of TDP-43, which promotes myelin formation. The hypomyelination of TDP-43cKO mice was also restored by NRXN1b supplementation in neurons. We further confirmed that TDP-43 stabilizes Nrxn1 mRNA by binding to the Nrxn1 3’untranslated region (3’UTR). Although TDP-43cKO exhibited impaired recognition memory, the supplementation of NRXN1 in the hippocampus recovered the memory disturbances. In conclusion, this study demonstrates the neuron–oligodendrocyte interaction mediated by neuronal TDP-43 via NRXN1 mRNA stabilization. These findings shed light on neuron–oligodendrocyte interaction in the disease mechanisms of ALS/FTLD.